Mechanical Stoking of Domestic Fuel - Joseph Harrington (Rocky Mountain Coal Mining Institute, 1925)
It is sufficiently correct to say that domestic solid fuel is universally hand fired and it is almost as correct to state that a very large proportion of hand-fired domestic fires are extremely inefficient and smoky. This is particularly true with raw bituminous coal for the fuel. The smokeless and efficient firing of domestic coal affords one of the most difficult problems confronting the combustion engineer. This is due to the universally constricted combustion space in the domestic furnace, the complete ignorance regarding the laws of combustion on the part of the average person, and the fact that the laws of efficient combustion are almost completely nullified under these conditions. It is well to familiarize ones self with these laws. These are: 1. The gradual introduction of the fuel to the furnace. 2. The admission and mixing of the right quantity of air with the coal gases. 3. A temperature high enough to permit complete combustion, and 4. A furnace space of volume sufficient to permit of the combustion gases and the oxygen getting together within the confines of the furnace. Even a casual inspection of the domestic heater will show that none of these essential things are present in proper degree, and this is the reason why the problem of domestic firing presents such difficulties. I have analyzed these conditions in a paper published by the Black Diamond, and which has already had wide distribution, so that I will not repeat the rather lengthy discussion in this paper. A survey of the entire field indicates very clearly that a reversal of existing methods and equipment must be had before any real improvement can be expected. It is my firm belief that in this instance above all others it is necessary to build the efficiency and smokelessness into the equipment in such a manner that its performance will be entirely independent of both skill and interest on the part of the operative. To attempt to educate every man, woman and child who periodically throws coal into a domestic furnace would be literally impossible. Much can be done, however, if we could teach the householder the simple essentials of alternate firing, which I have explained at length in the above mentioned paper. This would go a long way toward making the domestic furnace problem more satisfactory, as well as efficient and smokeless. Many will argue, and with good reason, that the domestic fuel should be prepared coke and with this I agree up to the limit imposed by the practical considerations of quantity production, price and the possibility of marketing the by-products. It will be obvious that if enough raw coal should be processed to provide all of the required domestic fuel that the amount of by-products recovered during the coking process would be so great that there would be little or no market at any price which would justify the manufacture of coke. If the by-products were wasted they would not only be a tremendous economic loss, but the price charged for the coke would probably be so high that the market would be limited, and this would defeat the very idea of the whole thing. Much can be done, however, in advancing the use of coke, but I believe that much more extensive and careful experimentization should be had in order to determine the right size and quality of coke for the various domestic furnaces. If coke were to be developed for extensive domestic consumption it is more than probable that the coking process should and could be stopped at a point where the volatile content of the coke would be sufficiently high to permit of prompt ignition and combustion in low draft installations. If the volatile content were from five to ten per cent a very different kind of coke would be produced from that which is now produced with perhaps one per cent of volatile. A skillful manipulation of this feature would make coke adaptable and satis-